Tourist flow and pure technical efficiency of critical infrastructure in Angola: A data envelopment approach using time series - Luzolo Sanches-António (Global Advances in Business Studies, 2026)
This study analyzes the effect of tourism flow on the pure technical efficiency of critical health and energy infrastructure in Angola, from 2013 to 2023. The input-oriented DEA-VRS model and Spearman's coefficient were used as complementary analytical tools. Each year was treated as a distinct DMU (Detailed Management Unit) to ensure greater discretionary power in the resulting efficient frontier. The variables considered include public hospitals and energy production (inputs), overnight stays by foreign tourists and jobs in the tourism sector (outputs), in addition to tourism flow as a control variable. The results reveal a virtually negligible correlation between technical efficiency and international tourist arrivals, in line with international evidence. It is concluded that tourism was not a direct determinant of the technical efficiency of the analyzed infrastructure, suggesting the need to explore indirect mechanisms, such as complementary investments or economies of scale.